2017
DOI: 10.1155/2017/4039048
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Method on Characteristic Parameters of Bacteria in Water by Multiwavelength Transmission Spectroscopy

Abstract: An analytic method together with the Mie scattering theory and Beer-Lambert law is proposed for the characteristic parameter determination of bacterial cells (Escherichia coli 10389) from multiwavelength transmission spectroscopy measurements. We calculate the structural parameters of E. coli cells, and compared with the microscopy, the relative error of cell volume is 7.90%, the cell number is compared with those obtained by plate counting, the relative error is l.02%, and the nucleic content and protein cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Therefore, variations in the chemical composition of the bacteria associated with protein and nucleic acid will determine changes in the absorption at different wavelengths in the UV‐Vis spectra in the range between 200 and 400 nm (Cheung et al, 2011; Markovitsi et al, 2010). Previous authors showed that the ratio between the wavelengths at 280:260 nm could be used as an indicator for changes in the proportion of nucleic acid and proteins during the growth of bacteria (Hu et al, 2017; Wilfinger et al, 1997). Therefore, changes observed in these wavelength regions can be attributed to the cells growing at different ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, variations in the chemical composition of the bacteria associated with protein and nucleic acid will determine changes in the absorption at different wavelengths in the UV‐Vis spectra in the range between 200 and 400 nm (Cheung et al, 2011; Markovitsi et al, 2010). Previous authors showed that the ratio between the wavelengths at 280:260 nm could be used as an indicator for changes in the proportion of nucleic acid and proteins during the growth of bacteria (Hu et al, 2017; Wilfinger et al, 1997). Therefore, changes observed in these wavelength regions can be attributed to the cells growing at different ratios.…”
Section: Resultsmentioning
confidence: 99%
“…However, at approximately 305 nm, all of the microorganisms displayed a dramatic spike in the increase of absorbance. This increase was more noticeable in the bacteria than the yeasts and may have been caused by the proteins and nucleic acids of the microorganisms [19]. Taken together, these criteria could be used to distinguish bacteria from yeast.…”
Section: Distinctive Qualities Of Microorganism Graphsmentioning
confidence: 91%
“…For all bacteria, absorbance increased at near infrared wavelengths. For several bacteria, absorbance increased in the visible light spectrum (380-700 nm) and for some, the increase occurred at ultraviolet (<380 nm) wavelengths (Figures 11,12,13,14,15,16,17,18,19,20,21,22,23,24,25, and 26, Table 8). Staphylococcus epidermidis exhibited the smallest increase in absorbance at near infrared wavelengths, which was barely noticeable from 1100 nm and decreased until 900 nm (Figure 12).…”
Section: Distinctive Qualities Of Microorganism Graphsmentioning
confidence: 99%
“…The generation of an accurate identification model for each microorganism must be based on a set of spectra that represents as many spectral variations as possible, which can be exhibited by each microorganism. The optical density at each wavelength point in the multi-wavelength transmission spectrum of bacterial suspensions is a function of the number, shape, size, internal structure, and the chemical composition of bacteria (Hu et al, 2017). Therefore, the bacterial identification model is characterized by the measured wavelength, and the optical density at the wavelength is the characteristic value, that is, the sample set is (λ i and τ(λ i )).…”
Section: Bacterial Identification Modelsmentioning
confidence: 99%